General chemistry : principles and modern applications - Petrucci, Ralph H.; Bissonnette, Carey; Herring, F. Geoffrey , 1939-; Madura, Jeffry D. (Pearson Canada, 2011)
The Molecule on the Front Cover is Paclitaxel, C47H51NO14 a chemotherapy drug that has been successful in treating breast, lung, and ovatian cancer. It is extracted from the bark of the Pacific Yew tree (Taxus brevifolia). Unfortunately, the bark of a 100-year-old Pacific Yew tree yields about 3 kg of bark and only 300 mg of paclitaxel, barely enough for a single dose of the drug (Taxol)